Influence of Salts on Growth, Yield and Metabolism of Wheat - Garg, B K; Kathju, S; Vyas, S P; Lahiri, A N (Annals of Arid Zone, 2016)
popular sail tolerant wheat cultivar, Kharchia 65, showed a highly variable sensitivity to different salts having a similar EC (10 mmhos/cm). Maximum adverse effects on growth and yield were brought about by Na2C03, NaHC03 and NaCl while Na2SO. and KCl caused negligible effects. CaCl2 and MgCl2 reduced dry matter but not grain yield. The magnitude of declines in chlorophyll and soluble protein and increases in free amino acids and RNA contents in leaves depended much On the salt species and age of plants. The general inhibition of nitrate reductase activity, by all salts and particularly by Na2C03 and NaHC03 at the advanced stages, suggested the possibility of performance alteration through deranged nitrogen metabolism.Effects on other enzymes were not consistent. Direct influences of the Na2C03 and NaHC03 on plants seem as important as their effects on soil physical conditions.